Analysis of Factors That Affecting The Interest Of Customers BCA Bank to Use Klik-Bca (Case Study: BCA Bank Kcp Kalimalang, Bekasi) - Ichwan Mochammad Buchori; Purwanto Purwanto (Forum Manajemen Indonesia (FMI), 2015)
This research has an objective to analyze the factors that affecting the interest of customers BCA bank yo use KlikBCA inKCP Kalimalang, Bekasi. BCA is the market leaader of internet banking in Indonesia with its KlikBCA. Now, the number of KlikBCA user is increasing both individual and business. Until 2009, the number of KlikBCA user increase become 1.7 million costumers from 1.2 million in 2008. The purpose of this research is to analyze the factors which have impact to the customers interest to use KlikBCA. Variables used in this this research are: independent variable (ease of use, convenience, privacy, and feature avaiability). While the dependent variable is the interest to use. The results are: ease of use and feature availability are not significant impact to the interest to use, while convenience and privacy are significant impact to the interest to use. Keywords: KlikBCA, ease of use, convenience, trust, and feature avaiability.